Effective Learning Strategies to Overcome Concentration Barriers in Tunagrahita Children at SLB Bhakti Luhur Madiun - Jawang, Rani (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to identify and analyze effective learning strategies in overcoming concentration barriers in children with disabilities at SLB Bhakti Luhur Madiun. Methodology: This study used a descriptive qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation with students with disabilities, teachers, and caregivers. Data analysis used the Miles and Huberman interactive model. Main Findings: The results showed that the implementation of various strategies such as direct learning, individualized teaching, behavior modification strategies, lecture method, and the use of learning media (pictures) were able to improve students' focus, motivation, and engagement. Regular evaluation by teachers is also proven to support learning effectiveness. Supporting factors include teacher commitment, small number of students, and comfortable classroom atmosphere. Meanwhile, the main obstacle is students' emotional instability. Novelty/Originality of this study: Previous research has discussed learning for children with special needs in general, but has not specifically examined effective learning strategies to overcome concentration barriers in students with intellectual disabilities in classroom practice. This gap highlights the need for more focused studies on applicable and contextual learning strategies. Therefore, this study aims to identify and analyze effective learning strategies in overcoming concentration barriers in children with intellectual disabilities at SLB Bhakti Luhur Madiun.